Nonlinear impacts of temperature on antibiotic resistance in Escherichia coli - Wenya Zhao; Shikan Zheng; Chengsong Ye; Jianguo Li; Xin Yu (Environmental Science and Ecotechnology)
The increase in bacterial antibiotic resistance poses a significant threat to the effectiveness of antibiotics, and there is growing evidence suggesting that global warming may speed up this process. However, the direct influence of temperature on the development of antibiotic resistance and the underlying mechanisms is not yet fully understood. Here we show that antibiotic resistance exhibits a nonlinear response to elevated temperatures under the combined stress of temperatures and antibiotics. We find that the effectiveness of gatifloxacin against Escherichia coli significantly diminishes at 42 °C, while resistance increases 256-fold at 27 °C. Additionally, the increased transcription levels of genes such as marA, ygfA, and ibpB with rising temperatures, along with gene mutations at different sites, explain the observed variability in resistance patterns. These findings highlight the complexity of antibiotic resistance evolution and the urgent need for comprehensive studies to understand and mitigate the effects of global warming on antibiotic resistance.